Venous Thrombotic Recurrence After Cerebral Venous Thrombosis: A Long-Term Follow-Up Study. Issue 2 (February 2017) - Palazzo, Paola; Agius, Pierre; Ingrand, Pierre; Ciron, Jonathan; Lamy, Matthias; Berthomet, Aline; Cantagrel, Paul; Neau, Jean-Philippe
Abstract : Background and Purpose—: After cerebral venous thrombosis (CVT), the risk of venous thrombotic events was estimated at 2% to 3% for a new CVT and 3% to 8% for extracranial events. However, because of the paucity of prospective studies, the clinical course of CVT is still largely unknown. We aimed to prospectively evaluate the rate of thrombosis recurrence in a cohort of CVT patients with a long-term follow-up and to detect predisposing factors for recurrence. Methods—: Consecutive CVT patients with complete clinical, radiological, biological, and genetic data were systematically followed up. New venous thrombotic events were detected after hospital readmission and imaging confirmation. Results—: One-hundred eighty-seven patients (mean age 45±18 years, 67% women) with angiographically confirmed CVT were included. Cause was found in 73% of patients. Coagulation abnormality and JAK2 gene mutation were detected in 20% and 9%, respectively. Median follow-up length was 73 months (range 1–247 months). Mean duration of the oral anticoagulant treatment was 14 months. Mortality rate was 2.5% per year, with 2% in-hospital mortality. During follow-up, CVT reoccurred in 6 patients, whereas 19 subjects had a symptomatic extracranial venous thrombotic event, with cumulative venous thrombotic recurrence rates of 3% at 1 year, 8% at 2 years, 12% at 5 years, and 18% at 10 years. A previous venous thrombotic event (hazard ratio, 2.8; P =0.018), presence of cancer or malignant hemopathies (hazard ratio, 3.2; P =0.039), and unknown CVT causes (hazard ratio, 2.81; P =0.024) were independently associated with recurrence. Conclusions—: In our cohort of CVT patients followed on average for >6 years, subjects with a previous venous thrombotic event, cancer/malignant hemopathies, and unknown CVT causes were found to be at higher risk of recurrence.